Design and analysis of fuel cell and photovoltaic based 110 V DC microgrid using hydrogen energy storage. Issue 3 (2nd June 2019) - Alam, Mohd; Kumar, Kuldeep; Dutta, Viresh
Abstract: A 110 V DC system has been designed for photovoltaic and fuel cell generators to operate DC loads such as LED lights, fans, laptop, and mobile phone charging in a DC microgrid. As the output characteristics of photovoltaic and fuel cell generators vary according to the operating conditions and connected load, the designing of the DC‐DC converter ensures that a stable DC voltage is available to the load under varying input voltage. A boost converter (with output power of 500 W) has therefore been fabricated to generate a stable 110 V output voltage for a widely varying input voltage (30‐85 V), which utilizes photovoltaic (750 Wp ) and a proton exchange membrane fuel cell (1 kW) power generators. The DC‐DC converter is designed to use either a silicon or silicon carbide power MOSFET by a suitably modified circuit, both are operated at 20 kHz switching frequency. The maximum converter efficiencies with silicon and silicon carbide MOSFETs are 95.7% and 97.8%, respectively. It is shown that the DC‐DC converter provides a stable operation with variations in operating conditions of photovoltaic and fuel cell generators and is well suited for application in a 110 V DC microgrid and Railways load applications. A feasibility study is performed for determining the sizes of photovoltaic and fuel cell generators to meet the Railways carriage load demand and found to be 5 kW photovoltaic and 5 kW fuel cell. Abstract : This article deals with the designing approach of a 110 V DC microgrid based on photovoltaic and fuel cell power generators.